An Analysis of the Determinants of Female Employment on Economic Growth in Central Sulawesi Province, 2015–2024 - Ni Luh Listya Dewi; Mohamad Ichwan Tandju; Yohan Yohan; Yunus Sading; Edhi Taqwa (Cakrawala Repositori IMWI)
This study examines the effect of female-related indicators on economic growth across regencies/cities in Central Sulawesi Province during 2015–2024. The independent variables include Female Life Expectancy (AHHP), Female Income Contribution (SPP), and Women in Professional Employment (PSTP). The study employs panel data sourced from the Central Statistics Agency and applies panel regression using the Random Effect Model (REM). Model selection is conducted through the Lagrange Multiplier (LM) test and the Hausman test. Hypothesis testing uses a 10 percent significance level. The results show that AHHP has a positive and not significant relationship with economic growth, indicating that improvements in female health have not translated into productive economic activity. SPP has a negative and significant relationship, indicating that increases in women’s income contribution are associated with a decline in economic growth. This finding reflects the concentration of women in low-productivity sectors and the dominant role of male income in driving economic growth. PSTP shows a negative and not significant relationship, indicating that the increase in women in professional employment has not contributed significantly to economic growth. Simultaneously, all independent variables do not have a significant effect on economic growth. The Adjusted R² value of 0.012059 indicates that the model has limited explanatory power. These findings confirm that the role of women in regional economic development remains suboptimal and is influenced by economic structure and labor quality. This study implies that the economic role of women has not been effectively integrated into high-productivity sectors, thereby limiting its impact on economic growth.